The internationalization of digital cultural content creators on global social media: navigating virtual outsidership in a borderless space - Yang, Rui; Shaheer, Noman; Wang, Yonggui; Li, Zhuyi Angelina (Journal of International Business Studies, 2025)
Global social media (GSM) is reshaping cultural industries by enabling digital content creators to share their content with global audiences. The resulting surge in content heralds a new era of experience-based consumption, where multicultural audiences continually seek novel experiences and rapidly shift to content that aligns with their evolving interests. The dynamic landscape of GSM indicates a substantial gap in digital internationalization research that largely focuses on overcoming the liability of outsidership to acquire new users while neglecting the challenge of sustaining long-term audience engagement. We address this gap by highlighting the unique challenge of virtual outsidership, which refers to the difficulty of attracting and retaining viewership amid shifting audience preferences. Extending product innovation research, we propose that creators can mitigate virtual outsidership by consistently producing novel content, though its effectiveness varies in GSM’s multicultural landscape. Specifically, novel content is more effective when audience preferences across countries align but less effective when cultural content significantly differs across regions. A panel data analysis of 355 YouTube channels across 24 countries supports our arguments. Our study advances digital internationalization research by identifying unique challenges in digital cultural industries and proposing strategies to sustain audience engagement in GSM’s dynamic environment.